The Usefulness of Intraoperative PTH as a Predictor for Successful Parathyroidectomy in Secondary Hyperparathyroidism - Chávez, Karla Verónica; Márquez-González, Horacio; Chavez-Tostado, Mariana (Frontiers in Surgery, 2021)
Introduction Secondary hyperparathyroidism (SHPT) is a multisystemic syndrome that affects calcium and bone homeostasis in patients with chronic kidney disease (CKD). Despite medical treatment, 1-2% of patients require parathyroidectomy annually. The use of an intraoperative paratohormone protocol (IOPTH) to predict cure still in debate, due to the lack of standardized protocols, the use of different assays and uneven PTH clearance. The aim of this study was to determine the diagnostic accuracy of an IOPTH in patients with SHPT for predicting successful surgery after parathyroidectomy. Methods. Thirty patients were enrolled. A prospective observational study (cohort) was performed in patients who were submitted to parathyroidectomy by an endocrine surgeon for SHPT. All were submitted to a bilateral neck exploration with a subtotal parathyroidectomy. Three IOPTH determinations were withdrawn: at anesthetic induction (PTH0), 15 minutes (PTH15), and 30 minutes (PTH30) after completion gland resection. Another sample was taken 24 hours after the procedure (PTH24), values <150pg/mL defined a successful surgery and patients were assigned to the successful or failure group. IOPTH drop was analyzed to predict successful surgery with drops of 70% and 90% at 15 and 30 minutes. Results. A total of 26 patients were included, nineteen patients were in the successful group. IOPTH showed a significant difference between groups in their absolute PTH15 and PTH30 values. A significant difference was also found in their PTH drop at 30 minutes (81% vs. 91% p=0.08). For predicting a successful surgery, having a PTH drop >90% at 30 minutes was the most significant factor (OR 3.0(1.5-4) IC 95%). Conclusions. This study points toward a stricter and staggered IOPTH protocol to predict a successful surgery. Our results suggest taking a PTH15 expecting a PTH drop of >90%. If this is not achieved, re-exploration and a PTH30 sample are suggested in order to accurately predict success.